Germline mutations and new copy number variants among 40 pediatric cancer patients suspected for genetic predisposition. Issue 4 (15th July 2019) - Gambale, Antonella; Russo, Roberta; Andolfo, Immacolata; Quaglietta, Lucia; De Rosa, Gianluca; Contestabile, Valentina; De Martino, Lucia; Genesio, Rita; Pignataro, Piero; Giglio, Sabrina; Capasso, Mario; Parasole, Rosanna; et al.
Abstract: Cancer predisposition syndromes (CPS) result from germline pathogenic variants, and they are increasingly recognized in the etiology of many pediatric cancers. Herein, we report the genetic/genomic analysis of 40 pediatric patients enrolled from 2016 to 2018. Our diagnostic workflow was successful in 50% of screened cases. Overall, the proportion of CPS in our case series is 10.9% (20/184) of enrolled patients. Interestingly, 12.5% of patients achieved a conclusive diagnosis through the analysis of chromosomal imbalance. Indeed, we observed germline microdeletions/duplications of regions encompassing cancer‐related genes in 50% of patients undergoing array‐CGH: EIF3H duplication in a patient with infantile desmoplastic astrocytoma and low‐grade Glioma; SLFN11 deletion, SOX4 duplication, and PARK2 partial deletion in three neuroblastoma patients; a PTPRD partial deletion in a child diagnosed with glioblastoma multiforme. Finally, we identified two cases due to DICER1 germline mutations. Abstract :